2013
DOI: 10.1051/epjconf/20134501037
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of water hammer in low pressurized pipe: comparison of SimHydraulics and Lax-Wendroff method with experiment

Abstract: Abstract. Article describes simulation of unsteady flow during water hammer with two programs, which use different numerical approaches to solve ordinary one dimensional differential equations describing the dynamics of hydraulic elements and pipes. First one is Matlab-Simulink-SimHydraulics, which is a commercial software developed to solve the dynamics of general hydraulic systems. It defines them with block elements. The other software is called HYDRA and it is based on the Lax-Wendroff numerical method, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In this study, the model is investigated with and without convection flow to determine its effect. Lax−Wendroff theorem, 34 which is a nonlinear equation with second-order accuracy in both space and time, was applied for the advective term in the model with convection flow. Meanwhile, in the model without convection flow, the region where only molecular diffusion occurs (1 mm in front of the pore inlet) was included because biomolecules are quickly consumed near the membrane inlet so that concentration gradients are formed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In this study, the model is investigated with and without convection flow to determine its effect. Lax−Wendroff theorem, 34 which is a nonlinear equation with second-order accuracy in both space and time, was applied for the advective term in the model with convection flow. Meanwhile, in the model without convection flow, the region where only molecular diffusion occurs (1 mm in front of the pore inlet) was included because biomolecules are quickly consumed near the membrane inlet so that concentration gradients are formed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This issue is quite complex and a large number of papers have already been published on this topic, e.g. [1], [2], [3], [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a conventional numerical method, the Lax-Wendroff Method (LWM) was widely used in computational fluid dynamics (CFD) [32]. However, only a few studies have briefly reported LWM in a water hammer simulation [12,33,34], without considering the convective acceleration terms, and it has hardly been applied in water hammer practices. Considering the real working conditions of water supply systems, it is more important to improve the accuracy of predictions on a water hammer in a pipeline with air content inside.…”
Section: Introductionmentioning
confidence: 99%